IMPROVING THE COMPETITIVENESS OF INDUSTRIAL ENTERPRISES IN UZBEKISTAN THROUGH STRATEGIC MANAGEMENT INSTRUMENTS - Orifov Javohirbek Uktam ugli; Yusupov Ulugbek Shukrullaevich (TADQIQOTLAR, 2026)
Abstract This article analyzes the issues of improving the competitiveness of industrial enterprises in Uzbekistan through the use of strategic management tools. The effective functioning of industrial enterprises and strengthening their positions in domestic and foreign markets are closely related to the proper application of strategic management methods. The study examined the importance of strategic management tools such as SWOT analysis, PEST analysis, Balanced Scorecard, and Porter’s model, and developed practical recommendations based on the example of industrial enterprises in Uzbekistan.